2017
DOI: 10.1039/c7sm00305f
|View full text |Cite
|
Sign up to set email alerts
|

Membrane structure formation induced by two types of banana-shaped proteins

Abstract: The assembly of banana-shaped rodlike proteins on membranes, and the associated membrane shape transformations, are investigated by analytical theory and coarse-grained simulations. The membrane-mediated interactions between two banana-shaped inclusions are derived theoretically using a point-like formalism based on fixed anisotropic curvatures, both for zero surface tension and for finite surface tension. On a larger scale, the interactions between assemblies of such rodlike inclusions are determined analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 59 publications
2
76
0
Order By: Relevance
“…Attractive membrane-mediated side-to-side pair interactions of arc-shaped particles have been obtained from energy minimization 66 . Side-to-side alignment has also been observed in simulations with arc-shaped inclusions in membranes 28,44,45 . In molecular dynamics (MD) simulations with a coarse-grained molecular model of N-BAR domains proteins on DLPC lipid vesicles, in contrast, a tip-to-tip alignment of proteins has been observed 48,67 , which may be affected by the direct, coarse-grained protein-protein interactions of the model.…”
Section: Discussionsupporting
confidence: 52%
“…Attractive membrane-mediated side-to-side pair interactions of arc-shaped particles have been obtained from energy minimization 66 . Side-to-side alignment has also been observed in simulations with arc-shaped inclusions in membranes 28,44,45 . In molecular dynamics (MD) simulations with a coarse-grained molecular model of N-BAR domains proteins on DLPC lipid vesicles, in contrast, a tip-to-tip alignment of proteins has been observed 48,67 , which may be affected by the direct, coarse-grained protein-protein interactions of the model.…”
Section: Discussionsupporting
confidence: 52%
“…The interactions between different curvature-generating proteins have been investigated only in a few studies. Two studies have reported the interactions of two types of protein rods including our previous study [46,52]. The coexistence of two types of rods induces phase separation [52] and straight and striped bump structures [46].…”
Section: Introductionmentioning
confidence: 99%
“…The protein assembly produces polygonal membrane tubes and polyhedral vesicles at a high protein density [58]. A positive surface tension destabilizes the rod assembly [59] and tubulation [54] whereas it stabilizes the striped structure formed by the two types of rods [46].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations